Downregulation of a Mitochondrial NAD+ Transporter (NDT2) Alters Seed Production and Germination in Arabidopsis. (17th February 2020) - Feitosa-Araujo, Elias; de Souza Chaves, Izabel; Florian, Alexandra; da Fonseca-Pereira, Paula; Condori Apfata, Jorge Alberto; Heyneke, Elmien; Medeiros, David Barbosa; Pires, Marcel Viana; Mettler-Altmann, Tabea; Neuhaus, H Ekkehard; Palmieri, Ferdinando; Arajo, Wagner L; et al.
Abstract: Despite the fundamental importance of nicotinamide adenine dinucleotide (NAD + ) for metabolism, the physiological roles of NAD + carriers in plants remain unclear. We previously characterized the Arabidopsis thaliana gene ( At 1g25380), named AtNDT2, encoding a protein located in the mitochondrial inner membrane, which imports NAD + from the cytosol using ADP and AMP as counter-exchange substrates for NAD + . Here, we further investigated the physiological roles of NDT2, by isolating a T-DNA insertion line, generating an antisense line and characterizing these genotypes in detail. Reduced NDT2 expression affected reproductive phase by reducing total seed yield. In addition, reduced seed germination and retardation in seedling establishment were observed in the mutant lines. Moreover, remarkable changes in primary metabolism were observed in dry and germinated seeds and an increase in fatty acid levels was verified during seedling establishment. Furthermore, flowers and seedlings of NDT2 mutants displayed upregulation of de novo and salvage pathway genes encoding NAD + biosynthesis enzymes, demonstrating the transcriptional control mediated by NDT2 activity over these genes. Taken together, our results suggest that NDT2 expression is fundamental for maintaining NAD + balance amongst organelles that modulate metabolism, physiology and developmental processes of heterotrophic tissues.